Measurement Quality Assurance in Construction - V. L. Solomakho; B. V. Tsitovich (Наука и техника)
Measurements in the process of production and testing of ready-made building materials and structures are considered to be an engineering base and control and evaluation of product parameters are to be carried out on its basis. Recommendations for normalization of a permissible measuring error in accordance with metrological problems are considered in the paper.